The fractional urinary fluoride excretion in young children under stable fluoride intake conditions - Villa A, Anabalo´n M, Cabezas L (Blackwell Synergy, 2000)
The purpose of this study was to determine the fraction of the total daily fluoride intake that is excreted through the urine (FUEF) of children aged 3– 5 years under usual intake conditions. Participating children were residents of an area with a fluoride (F) concentration of 0.5–0.6 mg/L in their drinking water. Assessments were made on two successive 24-h periods on 20 children, measuring the total amount of fluoride ingested through liquid and food consumption, and from ingestion of fluoridated toothpaste (500 mg F/g), together with the determination of the amount of fluoride excreted through urine.